2011
DOI: 10.1177/1947601911407323
|View full text |Cite
|
Sign up to set email alerts
|

Raf Family Kinases: Old Dogs Have Learned New Tricks

Abstract: First identified in the early 1980s as retroviral oncogenes, the Raf proteins have been the objects of intense research. The discoveries 10 years later that the Raf family members (Raf-1, B-Raf, and A-Raf) are bona fide Ras effectors and upstream activators of the ubiquitous ERK pathway increased the interest in these proteins primarily because of the central role that this cascade plays in cancer development. The important role of Raf in cancer was corroborated in 2002 with the discovery of B-Raf genetic muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
337
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 346 publications
(346 citation statements)
references
References 425 publications
(593 reference statements)
4
337
3
2
Order By: Relevance
“…This pathway regulates many fundamental cellular functions, including cell proliferation, and is dysregulated in approximately 50 % of human cancers 1. This pathway has thus been a key focus in cancer drug development.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This pathway regulates many fundamental cellular functions, including cell proliferation, and is dysregulated in approximately 50 % of human cancers 1. This pathway has thus been a key focus in cancer drug development.…”
mentioning
confidence: 99%
“…Owing to its important clinical implications, RAF dimerization has attracted enormous interest. RAF homo‐ and heterodimers show significantly higher kinase activity than monomers, and it has been shown that physiological RAF activation involves dimerization 1, 5. Dimer activity remains high even when one protomer (denoted as the activator) is kinase‐dead or inhibited, owing to allosteric transactivation of its binding partner (the receiver) 1, 5.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…16 This anti-apoptotic role may explain why A-Raf levels are elevated in a variety of malignancies. 16,[19][20][21] Both A-Raf and MST2 were shown to localize to the mitochondria in tumor cell lines as well as primary tumors. 16 A-Raf was reported to associate with the mitochondrial transport system proteins hTOM and hTIM, 22 but the physiological significance of this interaction is still unknown.…”
mentioning
confidence: 99%